Analisis komponen bioaktif dan atribut sensori seduhan kopi Arabika Kalosi Enrekang dengan pengolahan pascapanen berbeda [Analysis of bioactive compounds and sensory attributes of Kalosi-Enrekang Arabica coffee prepared different postharvest processing] - Yulianti, Yulianti; Adawiyah, Dede Robiatul; Herawati, Dian; Indrasti, Dias; Andarwulan, Nuri (Jurnal Teknologi & Industri Hasil Pertanian, 2023)
Postharvest processing affects the chemical components and sensory attributes of coffee beans. This  study aimed to evaluate the effect of postharvest processing on caffeoylquinic acids and alkaloids (bioactive compounds) and sensory attributes (aroma and taste) of brewed coffee. Coffee beans of Kalosi-Enrekang were processed using three postharvest processing methods (honey, natural, and full-washed), roasted at a medium degree, and brewed with tubruk brewing techniques. Bioactive compounds were analyzed using UPLC-PDA and sensory attributes were analyzed using the Quantitative Descriptive Analysis method. The data were analyzed using single-factor ANOVA and Principal Component Analysis. The research showed that postharvest processing did not affect the bioactive compound of brewed coffee. Postharvest processing affected the aroma and taste attributes of brewed coffee. Natural processing had dominant attributes of fruity, spicy, sweet, and caramelized. Honey processing had dominant attributes of nutty and roasted, while full-washed processing did not have dominant attributes. The result also showed that caffeoylquinic acids and alkaloids did not affect coffee brewed's aroma and taste attributes.